High-speed operation of a low-power 4-bit serial-to-parallel converter. - Vichot, P.A (IEEE Transactions on applied superconductivity)
This paper presents a high-speed low-power 4-bit superconducting serial-to-parallel converter (SPC) that has been demonstrated experimentally to operate at data rates up to 1 Giga-bits (Gb/s). The primary design goals for this device are high-speed operation, low-power dissipation, and high circuit yield for use as a core element in an address decoder or a demultiplexer. First, the circuit design and optimization are discussed. Simulated performance of the circuit shows proper operation at 20 Gb/s, with a discussion of its potential for use at even higher rates. The power dissipation is computed to be 28 μW in continuous operation and the predicted within-wafer yield is 95%. Measured results are then given for data rates of 100 Mb/s and 1 Gb/s.